2002
DOI: 10.1194/jlr.m200103-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

ApoB-48 and apoB-100 differentially influence the expression of type-III hyperlipoproteinemia in APOE*2 mice

Abstract: Apolipoprotein E (apoE) is essential for the clearance of plasma chylomicron and VLDL remnants. The human APOE locus is polymorphic and 5-10% of APOE*2 homozygotes exhibit type-III hyperlipoproteinemia (THL), while the remaining homozygotes have less than normal plasma cholesterol. In contrast, mice expressing APOE*2 in place of the mouse Apoe ( Apoe 2/2 mice) are markedly hyperlipoproteinemic, suggesting a species difference in lipid metabolism (e.g., editing of apolipoprotein B) enhances THL development. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…To our knowledge, in all other studies performed with the APOE2KI mice, liver morphology was not subject of investigation [3,[12][13][14]. Interestingly, already within 4 days of high-fat feeding these mice develop a marked liver phenotype characterised by steatosis, inflammation and early fibrosis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To our knowledge, in all other studies performed with the APOE2KI mice, liver morphology was not subject of investigation [3,[12][13][14]. Interestingly, already within 4 days of high-fat feeding these mice develop a marked liver phenotype characterised by steatosis, inflammation and early fibrosis.…”
Section: Discussionmentioning
confidence: 82%
“…Ninety homozygote female mice, 13 week old, were divided into groups of 10. One group was kept on standard chow.…”
Section: Mice and Dietmentioning
confidence: 99%
“…To test whether the ApoB-48 hypothesis was correct, this mouse model was used in a study in which ApoB-100 instead of ApoB-48 was expressed by deleting the gene responsible for ApoB-100 editing. This study showed that expression of solely ApoB-100 was not sufficient to reverse the hyperlipidemic phenotype, probably because ApoB-48 and ApoB-100 influence lipoprotein metabolism differently (76). These results indicate that the strong phenotype of APOE2ki mice is not entirely dependent on the difference in ApoB editing.…”
Section: Common Apoe Alleles In Mouse Modelsmentioning
confidence: 77%
“…CMRs are taken up from the bloodstream by liver cells mainly via membrane-bound LDL receptors [Martins et al, 2000]. It is known that this process requires the presence of apoE, as CMRs cannot bind to LDL receptors via apoB48 because this protein lacks the β2 domain responsible for this process [Hinsdale et al, 2002]. In our study, cells secreted 25% less apoE in the BHT--supplemented sample, but this did not affect the efficiency of CMR removal (Figure 5B).…”
mentioning
confidence: 50%